The Value of Islamic Education in Traditional Malay Poetry Concerning the Prohibition of Leaving Religious Teachings - Roziah, Roziah; Shomary, Sudirman; Hermaliza, Hermaliza; Oktadela, Resy; Nurhidayah, Nurhidayah; Dewi, Aulia Putri (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2025)
This study aims to explore taboos and prohibitions in traditional Malay poetry that embody Islamic educational values. The traditional poetry analyzed includes gurindam, pantun, poetry, and expressions that were once integral to daily life but have now become increasingly rare. The Islamic educational values examined in this study encompass aspects of faith (aqidah), acts of worship (ibadah), and commendable conduct (akhlaq). This research employs both qualitative and quantitative approaches, utilizing a problem-solving methodology that includes literature review, content analysis, and comparative analysis. Data were collected from gurindam manuscripts, pantun, poetry, and Malay expressions that align with the teachings of the Quran, supported by the translation and interpretation of Ibn Kathir. The analytical process involves investigating and documenting relevant Quranic verses and Hadith that reinforce taboos and prohibitions found in traditional poetry, followed by formulating research findings. The study identifies the following key findings: (a) The Islamic educational values related to faith include: (1) The prohibition against associating partners with God (shirk) in Malay culture; (2) The prohibition against apostasy (riddah) among Malays. (b) The Islamic educational values related to acts of worship include: (1) The prohibition against neglecting prayer (salah); (2) The prohibition against neglecting fasting (sawm); (3) The prohibition against neglecting almsgiving (zakat); (4) The prohibition against neglecting the Hajj pilgrimage. (c) The Islamic educational values related to morality (akhlaq), specifically the prohibition against engaging in sinful or immoral acts. The findings of this study have implications for Malay Literature courses, where students will be introduced to taboos and prohibitions embedded in Malay culture. These values will be disseminated through interactive videos and digital media promotions. The utilization of digital platforms is expected to bridge the generational gap, fostering greater interest among younger generations in understanding and contributing to the preservation of this cultural heritage.Penelitian ini merupakan upaya investigasi pantang larang dalam puisi tradisional Melayu bermuatan nilai pendidikan Islam. Puisi tradisional yang ditelaah meliputi gurindam, pantun, syair, dan ungkapan yang dulunya selalu digunakan dalam kehidupan sehari-hari, sekarang jarang sekali terdengar di telinga. Muatan pendidikan Islam yang dimaksud dalam kajian ini merujuk pada keimanan, amal ibadah dan perbuatan terpuji. Penelitian ini menggunakan pendekatan kualitatif dan kuantitatif dengan pendekatan pemecahan masalah yaitu tinjauan pustaka, analisis isi, analisis komparatif. Data yang dikumpulkan dari buku-buku gurindam, pantun, syair, dan ungkapan Melayu yang diduga sejalan dengan ayat alquran beserta terjemah serta tafsir Ibnu Katsir. Langkah analisis meliputi Menyelidiki dan mendokumentasikan mengutip ayat Alquran dan Hadis yang mendukung pantang larang dalam puisi tradisional serta merumuskan hasil penelitian. Hasil kajian yang ditemukan adalah (a) Nilai pendidikan Islam terkait akidah meliputi (1) Orang Melayu dilarang menyekutukan Tuhan; (b) Orang Melayu dilarang murtad; (b) Nilai pendidikan Islam terkait ibadah meliputi (1) Orang Melayu dilarang meninggalkan prayer, (2) Orang Melayu dilarang meninggalkan puasa, (3) Orang Melayu dilarang meninggalkan zakat, dan (4) Orang Melayu dilarang meninggalkan haji; (c) Nilai pendidikan Islam terkait Akhlak yaitu larangan berbuat fasik. Hasil kajian ini dapat diimplikasikan pada mata kuliah Sastra Melayu. Mahasiswa akan diajarkan tentang pantang larang dalam budaya Melayu, yang nantinya akan dipromosikan dalam bentuk video interaktif dan promosi di platform media digital. Promosi melalui Platform media digital dapat menjembatani kesenjangan antara generasi tua dan muda, serta menarik minat generasi muda dalam memahami dan turut melestarikan warisan budaya ini.